Business feasibility and strategic development analysis of kebab kota raja culinary msme in the digital era - Prapdopo Prapdopo; Surahman Surahman; Nadila Nadila; Nis Faradilah; Armini Ningsih (Institute of Computer Science (IOCS), 2025)
The food sector in Indonesia has experienced significant growth over the past few decades, supported by stable economic growth, changes in lifestyle, and increasing urbanization. Micro, Small, and Medium Enterprises (MSMEs) in the food sector contribute significantly to the economy, accounting for approximately 61.07% of the Gross Domestic Product and absorbing 97% of the workforce. This study aims to develop an integrated and contextual business viability model for food MSMEs by combining aspects of market, technical, financial, managerial, environmental, and risk and sustainability factors, using use of digital marketing strategis, good financial management of the business. The financial viability analysis using NPV, IRR, Payback Period, and BEP methods indicates that the business is feasible and profitable. The SWOT analysis highlights opportunities for franchise development and digital market expansion, but also identifies challenges such as intense competition and fluctuating raw material prices. This study provides both theoretical and practical contributions for the development of adaptive, efficient, and sustainable business strategies for food MSMEs in the digital era of Indonesia.